AL-QURAN DAN EKARISTI SEBAGAI PUSAT HIDUP BERIMAN DAN KEROHANIAN UMAT MUSLIM DAN KRISTIANI - Pranoto, Stepanus Sigit (Jurnal Teologi (Journal of Theology), 2015)
This article is an attempt to explore and practice of comparative theology. Comparative theology itself is unique in terms of its sources and methods, in which theological reflection is built on the basis of a comparison of more than one religious traditions. Moreover, comparative theology emphasizes practice rather than theory. According to the author, theology comparative is a contextual theology that can be developed in plural Indonesian society. In this practice, the author chooses the Quran and the Eucharist as the starting point of the discussion.